Non-ST segment elevation myocardial infarction induced by carbon monoxide poisoning - Gamze Küçükosman; Bengü Gülhan Aydın; Hilal Ayoğlu (KARE Publishing, 2020)
Carbon monoxide (CO) poisoning is the most common cause of poisoning-related death in the world. Cardiovascular complications of CO intoxication includes myocardial damage, left ventricular dysfunction, pulmonary edema, and arrhythmias. The carboxyhemoglobin level does not correlate with the clinical severity of CO intoxication. This case report presents a patient with acute myocardial infarction secondary to carbon monoxide poisoning who was successfully treated with coronary bypass surgery.